Analysis of Factors Related to Patient Satisfaction in Radiology Unit of Prof Dr. W. Z. Johannes Hospital, Kupang - Laitabun, Yoel Midel; Pellokila, Marthen; Paun, Rafael (Health Notions, 2018)
Patient satisfaction depends on the quality of service. This study aimed to analyze the factors associated with patient satisfaction with service in radiology installations, using cross sectional design. Data were analyzed using Chi square test. The results showed p-value = 0.019, so it is concluded that there was a correlation between the level of patient satisfaction with waiting time in radiology installations. If the waiting time is long, then the patient will feel dissatisfied, on the contrary if the service time is done quickly hospital, then the patient will feel satisfied.